2019
DOI: 10.3389/fmicb.2019.02226
|View full text |Cite|
|
Sign up to set email alerts
|

Forest Soil Fungal Community Elevational Distribution Pattern and Their Ecological Assembly Processes

Abstract: Soil fungi play vital roles in natural ecosystems, however, their community distribution patterns along different environmental gradients and ecological assembly processes remain unclear. In this study, Illumina MiSeq sequencing was used to investigate the soil fungal community structures of five different forest types along an elevational gradient, and a framework based on a null model was adopted to quantify the relative contribution of deterministic and stochastic ecological assembly processes. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…In addition, many Basidiomycota species are ectomycorrhizal and may then be disturbed by the topsoil storage. Among the Basidiomycota, the class of Agaricomycetes was dominant, which is frequently reported in similar studies (Karst et al, 2013;Ko et al, 2017;Sheng et al, 2019).…”
Section: Studies Discussing Variations In Microbial Taxa Composition ...supporting
confidence: 70%
See 1 more Smart Citation
“…In addition, many Basidiomycota species are ectomycorrhizal and may then be disturbed by the topsoil storage. Among the Basidiomycota, the class of Agaricomycetes was dominant, which is frequently reported in similar studies (Karst et al, 2013;Ko et al, 2017;Sheng et al, 2019).…”
Section: Studies Discussing Variations In Microbial Taxa Composition ...supporting
confidence: 70%
“…Our DISTLM analysis also detected an effect of soil pH on the bacterial community structure. Soil pH is commonly reported as regulating the structure of microbiota communities (Lauber et al, 2008;Rousk et al, 2010;Sheng et al, 2019). In our case, it is interesting to note that Acidobacteria, the second most important bacterial phylum in the studied topsoils, declined after storage in topsoil 2 where the pH value raised from 5.2 to 6.5.…”
Section: Studies Discussing Variations In Microbial Taxa Composition ...mentioning
confidence: 48%
“…In this study, the dominant micro ora of soil fungus were Basidiomycota and Ascomycota, the contents of them have difference with signi cance. The results showed that the dominant phyla of fungus were different under different stand types, which is consistent with the results of Sheng's study [35]. The dominant soil fungus under the soil of Betula dahurica, Pinus tabuliformis and Juglans mandshurica forest are Ascomycota, followed by Basidiomycota, the same situation appeared in tropical forest soil, subtropical forest soil in Australia, Guandi mountain forest soil and aeolian sand area in Northwest Liaoning.…”
Section: Soil Community Structuresupporting
confidence: 87%
“…Some studies have also showed that soil total nitrogen and nitrate nitrogen are the key drivers for α-diversity of saprophytic and pathogenic fungi along altitude gradients, respectively [ 41 ]. The β-diversity of soil fungi was found to be driven by environmental factors, geographic distance, or their combination along altitude gradients [ 42 , 43 , 44 ]. The driver divergence of turnover and nestedness components of soil fungal β-diversity has been validated at regional scales [ 30 ], but it has not been validated along altitude gradients.…”
Section: Introductionmentioning
confidence: 99%